A brief review of the tribe Telsimiini (Coleoptera: Coccinellidae) of the Indian subcontinent, including three new species of Telsimia Casey from South India - Poorani, J.; Thanigairaj, R. (Zootaxa, 2023)
Species of the tribe Telsimiini (Coleoptera: Coccinellidae) of the Indian subcontinent, all belonging to a single genus, Telsimia Casey, 1899, are briefly reviewed. Three new species, Telsimia pygmaea sp. n., Telsimia intricata sp. n. (both from Tamil Nadu) and Telsimia mudigerensis sp. n. (from Karnataka), are described and illustrated from southern India. The immature stages of Telsimia pygmaea sp. n. and Telsimia intricata sp. n. are also illustrated along with details of their associated hosts and host plants. Telsimia sichuanensis Pang & Mao, 1979 is a new addition to the Indian fauna (from the northeastern state of Manipur). An updated checklist of the Telsimiini of the Indian Subcontinent is provided.